Bioregionalism: Practical Environmental Ethics with an Underlying Pragmatic Ideal - Sarkar, Ipsita; Behura, Ajit (Problemy Ekorozwoju, 2018)
The theories of environmental ethics battle about appropriate value of nature and consequently the appropriate human attitude towards nature. However, they are unable to influence actual human behavior towards nature. So what we need here is not another theory about what possesses intrinsic value or, what ought to influence behavior, but some strategies that can actually influence individual behavior, their attitude about unlimited consumption, and their present environmentally destructive lifestyles. Bioregionalism may be one such strategy. Bioregionalism, with its ethics of reinhabitation and precondition of identification with the local place ensures an emotional connection with nature, which may just be the answer to human induced environmental degradation. Further, such practical ethics has an underlying pragmatic ideal. Pragmatism is the school of thought that roughly holds that our ideas, theories, and world views should be examined in the light of their practical implications in our lives.